Work Conditions and Librarians' Competencies in Service Delivery in University Libraries in North Central Nigeria - Annabel Onyeisi Ijeh; Israel Odede; Ishioma Faith Irogbo; Esoswo Francisca Ogbomo (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2026)
Background of the study: University library effectiveness is determined by librarians' competencies, which are influenced by working conditions. Different work environments in Nigerian universities affect service quality, but empirical data on these impacts in North Central Nigeria is limited. Purpose: This study investigated the influence of work conditions on librarians’ competencies in service delivery in university libraries in North Central Nigeria. Specific objectives were to examine librarians’ competencies, assess work conditions, and determine their relationship. Method: Adopting a correlational survey design, this study used total enumeration for all 301 librarians in federal and state university libraries in North Central Nigeria. A structured, validated questionnaire was used; 251 copies were usable. Descriptive and inferential statistics (simple linear regression, ANOVA) analyzed the data. Findings: Librarians demonstrated high professional competence in information retrieval, ICT, communication, and resource management. Work conditions were generally favorable regarding lighting, ventilation, temperature, interpersonal relationships, and workspace quality, though remuneration and allowances were less satisfactory. A significant positive relationship exists between work conditions and competencies. Conclusion: The study concludes that conducive work conditions strongly enhance librarians’ competencies and overall service delivery in university libraries in North Central Nigeria. It thus advises the constant betterment of working conditions, the supply of useful tools and technologies, and better welfare of the librarians to maintain high quality service delivery.